Prognostic significance of extracapsular spread of lymph node metastasis from oral squamous cell carcinoma in the clinically negative neck. Issue 6 (June 2017) - Suton, P.; Salaric, I.; Granic, M.; Mueller, D.; Luksic, I.
Abstract: The presence of extracapsular spread (ECS) in patients with oral squamous cell carcinoma (OSCC) indicates a poor prognosis and is associated with a higher risk of regional recurrence and distant metastasis. The aim of this study was to analyse this important feature of cervical lymph nodes in the clinically node-negative setting. The study included 61 patients with clinically T1–T3N0 OSCC who underwent primary surgical treatment; 52 were male and nine were female, and their median age was 57 years. The 5-year disease-free survival, disease-specific survival, and overall survival rates were 30.6%, 28.3%, and 14.3%, respectively, in the ECS group compared to 61.9%, 61.9%, and 48.2%, respectively, in the pN+/ECS-negative group and 76.7%, 81.9%, and 47.0%, respectively, in the pN0 group. The differences between the survival curves were highly significant ( P  = 0.023, P  = 0.003, and P  = 0.029, respectively). The incidence of local (50% vs. 14.9%, P  = 0.011) and regional (28.6% vs. 2.1%, P  = 0.008) recurrence was significantly greater in the ECS group compared to the other subgroups of patients. Furthermore, the time to recurrence was significantly shorter in the ECS subjects. The presence of ECS in patients with oral cancer indicates a poor prognosis. ECS is a frequent feature in clinically node-negative settings and may be more common in smaller lymph nodes than is generally appreciated.